Optimal secondary prevention medication use in acute myocardial infarction patients with nonobstructive coronary artery disease is modified by management strategy: insights from the TRIUMPH Registry. Issue 6 (7th April 2017) - Pitts, Reynaria; Daugherty, Stacie L.; Tang, Fengming; Jones, Philip; Ho, P. Michael; Tsai, Thomas T.; Spertus, John; Maddox, Thomas M.
Abstract : Background: Patients with acute myocardial infarction (AMI) and nonobstructive coronary artery disease (nonobCAD) may be perceived to be at lower risk for cardiac events, relative to those with obstructive CAD (obCAD), and thus less likely to receive optimal preventive medications in the year following AMI. Hypothesis: We aimed to determine if AMI patients with nonobCAD, compared to obCAD, received lower rates of prevention medications in the year following AMI. Methods: We compared optimal prevention medication use at hospital discharge, 1, 6, and 12 months after hospitalization. Optimal medication use was defined as the receipt of all prevention medications for which that patient was eligible (eg, aspirin, clopidogrel, statins, β‐blockers, and angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers). We used multivariable logistic regression analyses to determine the association between nonobCAD to medication use and adjusted for potential confounders. Results: Three thousand six hundred thirty AMI patients were studied, of whom 200 (5.2%) had nonobCAD. Fewer nonobCAD patients received optimal medication use compared to obCAD patients at discharge (31% vs 65%, P < 0.001), driven primarily by lower rates of clopidogrel use (40.5% vs 83.3%, P < 0.001). After adjustment for percutaneous coronary intervention (PCI), differences in medication use were similar at discharge and 1 year after hospitalization. Stratified analyses by receipt of PCI suggested patients confined to medical management had less optimal medication use, regardless of their CAD burden. Conclusions: Lower rates of unadjusted optimal medication use were seen in nonobCAD patients, driven by low clopidogrel use among medically managed patients, suggesting improvement efforts should focus on these patients.